Pharmacological Evaluation of Safoof-e-Pathar Phori- A Polyherbal Unani Formulation for Urolithiasis - Ahmad, Wasim; Khan, Mohammad Ahmed; Ashraf, Kamran; Ahmad, Ayaz; Daud Ali, Mohammad; Ansari, Mohd Nazam; Kamal, YT; Wahab, Shadma; Zaidi, SM Arif; Mujeeb, Mohd.; Ahmad, Sayeed (Frontiers in Pharmacology, 2021)
Safoof-e-Pathar phori (SPP) is a Unani poly-herbomineral formulation, which has been used as a medicine because of its antiurolithiatic activity as per Unani Pharmacopoeia since a long time. This powder formulation is prepared using six different plant/mineral constituents. In this study, we explored the antiurolithiatic and antioxidant potentials of SPP (at 700 and 1000 mg/kg) in albino Wistar rats with urolithiasis induced by 0.75% ethylene glycol (EG) and 1% ammonium chloride. Long-term oral toxicity studies were performed according to Organisation for Economic Co-operation and Development (OECD) guidelines for 90 days at the oral dose of 700 mg/kg of SPP. EG urolithiatic toxicant group had significantly higher levels of urinary calcium, serum creatinine, blood urea, and tissue lipid peroxidation and significantly (P < 0.001 vs control) lower levels of urinary sodium and potassium than normal control. Histopathological examination revealed presence of refractile crystals in the tubular epithelial cell and damage to proximal tubular epithelium in toxicant group but not in SPP treatment groups. Treatment of SPP at 700 and 1000 mg/kg significantly (P < 0.001 vs toxicant) reduced lower urinary calcium, serum creatinine, blood urea, and lipid peroxidation in urolithiatic rats 21 days after induction of urolithiasis compare to toxicant. Long-term oral toxicity study revealed normal growth of animals without any significant change in haematological, hepatic, and renal parameters; there was no evidence of abnormal histology of heart, kidney, liver, spleen, or stomach tissues. These results suggested the usefulness of SPP as an antiurolithiatic and an antioxidant agent, and long-term daily oral consumption of SPP was found to be safe in albino Wistar rats up to 3 months. Thus, SPP may be safe for clinical use as an antiurolithiatic formulation.